Предварительные результаты исследования многослойного поселения Кощеевка 8 в Фастовском р-не Киевской обл. - Лысенко, С.Д.; Шкляревский, Е.И.; Квитницкий, М.В.; Черновол, Д.К. (Археологічні дослідження в Україні, 2009)
In 2008, Fastiv archaeological expedition conducted protective excavations on the construction site of the granite processing plant and on the territory of finished goods warehouse at Koshchiiv Granite Open-cast Mine. Koshchiivka 8 settlement of over 3 hectares was studied fully. More than 150 objects of Trypillya culture (stage CII), Bronze Age (cultural circles Babynska and Tshynetska), and of Ancient Rus time (from the middle of the 11th c. to the middle of the 13th c.) were revealed. Also the materials of circles of the Corded Ware culture and the Early Scythian time were found.